The Influence of 6 Variables on Early Marriage Decision Making in Young Women in Puskesmas Meninting - Kusumarini, Baik Dinda (Jurnal Ayurveda Medistra, 2021)
Early marriage is a marriage that is carried out in adolescence, the factors that influence early marriage are socio-economic and demographic conditions. This study aims to determine the direct and indirect influence and magnitude of the role of information media, the role of health workers, the social environment and self-concept of early marriage decision making in ​​West Lombok pushing health centers in 2019. This type of research uses quantitative methods with analytical descriptive techniques, with cross sectional research designs (cross section). The population in this study were young women at Meninting Community Health Center, which numbered 150 people. The direct influence of media information (19.64%), the role of health workers (21.90%), social environment (15.37%), family role (9.67%), self-concept (15.43%). The direct influence of adolescent decision making in early marriage 82.00%. While the indirect effect is 1.91%, direct and indirect influence is 83.91%. The factors that most influence adolescent decision making in early marriage are the role of health workers, the better the role of health workers , the better the teenagers in making decisions. Researchers suggest health workers as motivators and health care providers are expected to be able to further improve health promotion to adolescents.